Shiga toxin of enterohaemorrhagic Escherichia coli directly injures developing human erythrocytes. (29th April 2016) - Betz, Josefine; Dorn, Isabel; Kouzel, Ivan U.; Bauwens, Andreas; Meisen, Iris; Kemper, Björn; Bielaszewska, Martina; Mormann, Michael; Weymann, Lena; Sibrowski, Walter; Karch, Helge; Schlenke, Peter; et al.
Summary: Haemolytic anaemia is one of the characteristics of life‐threatening extraintestinal complications in humans during infection with enterohaemorrhagic Escherichia coli (EHEC). Shiga toxins (Stxs) of EHEC preferentially damage microvascular endothelial cells of the kidney and the brain, whereby occluded small blood vessels may elicit anaemia through mechanical erythrocyte disruption. Here we show for the first time that Stx2a, the major virulence factor of EHEC, is also capable of direct targeting developing human erythrocytes. We employed an ex vivo erythropoiesis model using mobilized CD34 + haematopoietic stem/progenitor cells from human blood and monitored expression of Stx receptors and Stx2a‐mediated cellular injury of developing erythrocytes. CD34 + haematopoietic stem/progenitor cells were negative for Stx2a receptors and resistant towards the toxin. Expression of Stx2a‐binding glycosphingolipids and toxin sensitivity was apparent immediately after initiation of erythropoietic differentiation, peaked for basophilic and polychromatic erythroblast stages and declined during maturation into orthochromatic erythroblasts and reticulocytes, which became highly refractory to Stx2a. The observed Stx‐mediated toxicity towards erythroblasts during the course of erythropoiesis might contribute, although speculative at this stage of research, to the anaemia caused by Stx‐producing pathogens.